Facilitation by intracellular carbonic anhydrase of Na-HCO co-transport but not Na/H exchange activity in the mammalian ventricular myocyte - Villafuerte, F; Swietach, P; Youm, J; Ford, K; Cardenas, R; Cobden, P; Rohling, M; Vaughan-Jones, R; Supuran, C (2014)
Carbonic anhydrase enzymes (CAs) catalyse the reversible hydration of CO to H and HCO ions. This catalysis is proposed to be harnessed by acid/base transporters, to facilitate their transmembrane flux activity, either through direct protein-protein binding (a 'transport metabolon') or local functional interaction. Flux facilitation has previously been investigated by heterologous co-expression of relevant proteins in host cell lines/oocytes. Here, we examine the influence of intrinsic CA activity on membrane HCO or H transport via the native acid-extruding proteins, Na-HCO cotransport (NBC) and Na/H exchange (NHE), expressed in enzymically isolated mammalian ventricular myocytes. Effects of intracellular and extracellular (exofacial) CA (CA and CA) are distinguished using membrane-permeant and -impermeant pharmacological CA inhibitors, while measuring transporter activity in the intact cell using pH and Na fluorophores. We find that NBC, but not NHE flux is enhanced by catalytic CA activity, with facilitation being confined to CA activity alone. Results are quantitatively consistent with a model where CA catalyses local H ion delivery to the NBC protein, assisting the subsequent (uncatalysed) protonation and removal of imported HCO ions. In well-superfused myocytes, exofacial CA activity is superfluous, most likely because extracellular CO/HCO buffer is clamped at equilibrium. The CA insensitivity of NHE flux suggests that, in the native cell, intrinsic mobile buffer-shuttles supply sufficient intracellular H+ ions to this transporter, while intrinsic buffer access to NBC proteins is restricted. Our results demonstrate a selective CA facilitation of acid/base transporters in the ventricular myocyte, implying a specific role for the intracellular enzyme in HCO3 - transport, and hence pHi regulation in the heart. © 2013 The Authors. The Journal of Physiology published by John Wiley and Sons Ltd on behalf of The Physiological Society.